Is There a Role for Treating Inflammation in Moyamoya Disease?: A Review of Histopathology, Genetics, and Signaling Cascades - Young, Adam M.; Karri, Surya K.; Zhao, I; Ogilvy, Christopher S. (Frontiers in Neurology, 2013)
Moyamoya disease is a slowly progressing steno-occlusive condition affecting the cerebrovascularture. Affecting the terminal internal carotid arteries (ICA) and there branches, bilaterally, a resulting in a fine vascular network in the base of the brain to allow for compensation of the stenosed vessels. While there is obvious evidence of the involvement of inflammatory proteins in the condition, this has historically not been acknowledged as a causal factor. Here we describe the fundamental histopathology, genetics and signaling cascades involved in moyamoya and debate whether these factors can be linked as causal factor for the condition or whether they are simply a secondary result of the ischemia described in the condition. A particular focus has been placed on the multitude of signaling cascades linked to the condition as these are viewed as having the greatest therapeutic potential. As such we hope to draw some novel insight into potential diagnostic and therapeutic inflammatory targets in the condition.